Analysis of the Role of Internal Auditors as Consultants for the North Sulawesi Regional Government - Novia Kokali; Hendrik Gamaliel; Olivia Y. M. Sardjono (LP2M IBK Nitro, 2026)
The demands on the role of Government Internal Supervisory Apparatus (APIP) have changed over time, not only as a provider of assurance but also in conducting consultation activities. With this paradigm shift, auditors are not only providers of assurance but also play the role of service consultants by offering advice or guidance related to issues faced by organizations. This study aims to determine the role of internal auditors as consultants for the North Sulawesi Regional Government. This type of research is qualitative descriptive. based on the results of the study show that the role of APIP of the Regional Inspectorate of North Sulawesi Province as a consultant improves the quality of APIP as an internal audit of the government. The role of an inspectorate consultant can help minimize and prevent errors in the duties and functions of the OPD. In addition, the impact of the change in APIP's role as a consultant is also considered positive, APIP is not only seen as a fault seeker, but with the role of a consultant, namely a solution provider or recommendation, OPD is increasingly open to consulting about the mistakes they face. The obstacles faced by the Inspectorate in carrying out its role as a consultant are limited Human Resources, lack of budget, and time that APIP has in carrying out its role as a consultant.